Comparison of botulinum toxin (BoNT) injection and lateral internal sphincterotomy (redo-LIS) for recurrent anal fissure treatment - Alyanak, Ahmet; Gulen, Merter; Ege, Bahadır (Frontiers in Surgery, 2022)
Abstract: Objective: Today’s gold standard for treating chronic anal fissure is the Lateral Internal Sphincterotomy (LIS). Botulinum Toxin (BoNT) injection is, on the other hand, an alternative treatment for patients who do not want to have surgical treatment, patients undergoing chemotherapy, patients of high risk for surgery, and those who have the risk of anal incontinence (e.g. elderly, past anorectal surgery, vaginal multiple births, etc.). The objective of this work is to compare the effectiveness of BoNT and redo-LIS for treatment of post-LIS recurrent chronic anal fissure, and reveal differences if any. This study aims to compare redo-LIS and BoNT injection for treating post-LIS recurrent anal fissure. Material and method: Nineteen patients who received LIS treatment and then redo-LIS or BoNT injection due to recurrence in the follow-up were included in this study as they met the criteria for doing so. Their data on age, sex, anal incontinence scores and pain (VAS score) score as well. Results: During the 6-month post-surgery follow-up period, there was statistically significant difference (p<0.01) between groups by pain. No deterioration in the incontinence scores of patients in the group during the 6-month post-surgery period. Conclusion:This study demonstrates that redo lateral internal sphincterotomy (LIS) is a reliable method for patients who received LIS but developed recurrent chronic anal fissure, and achieves successful results in terms of recurrence and relief of pain.